Role of methyl jasmonate in the expression of mycorrhizal induced resistance against Fusarium oxysporum in tomato plants - Nair, Aswathy; Kolet, Swati P.; Thulasiram, Hirekodathakallu V.; Bhargava, Sujata (Physiological and Molecular Plant Pathology, 2015)
Arbuscular mycorrhiza (AM) colonization led to a decrease in the severity of fusarium wilt disease caused by Fusarium oxysporum f. sp. lycopersici in tomato plants. The involvement of two plant defense hormones, namely methyl jasmonate (MeJA) and salicylic acid (SA), in the expression of mycorrhiza induced resistance (MIR) against this vascular pathogen was studied in the AM colonized and non-colonized (controls) plants. Activity of lipoxygenase (LOX), which plays a role in jasmonic acid (JA) biosynthesis, as well as levels of methyl jasmonate (MeJA) increased in AM colonized plants as compared to controls, but did not show any further changes in response to F. oxysporum inoculation. On the other hand, activity of phenylalanine ammonia lyase (PAL), which is an enzyme from salicylic acid (SA) biosynthetic pathway, as well as SA levels, increased in both controls and AM colonized plants in response to application of F. oxysporum spores. Hence the JA and not the SA signalling pathway appeared to play a role in the expression of MIR against this vascular pathogen. The resistance observed in AM colonized plants was completely compromised when plants were treated with the JA biosynthesis inhibitor salicylhydroxamic acid (SHAM). This confirmed that the AM-induced increase in JA levels was involved in the expression of resistance toward F. oxysporum. The SA response gene pathogenesis-related 1 (PR1) showed an increased expression in response to F. oxysporum infection in SHAM treated AM colonized plants as compared to plants that were not treated with this JA inhibitor. This suggested the possibility that JA inhibited SA responses, at least in the roots. AM colonization therefore appeared to prime plants for improved tolerance against the vascular pathogen F. oxysporum, which was mediated through the JA signalling pathway. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Fusarium wilt; Glomus fasciculatum; Methyl jasmonate; Mycorrhiza induced resistance; Salicylic acid; Tomato

Plant-pathogen interactions: microRNA-mediated trans-kingdom gene regulation in fungi and their host plants - Mathur, Monika; Nair, Aswathy; Kadoo, Narendra (Genomics, 2020)
MicroRNAs (miRNAs) have been prevalently studied in plants, animals, and viruses. However, recent studies show evidences of miRNA-like RNAs (milRNAs) in fungi as well. It is known that after successful infection, pathogens hijack the host machinery and use it for their own growth and multiplication. Alternatively, resistant plants can overcome the pathogen attack by a variety of mechanisms. Based on this prior knowledge, we computationally predicted milRNAs from 13 fungi, and identified their targets in transcriptomes of the respective fungi as well as their host plants. The expressions of the milRNAs and targets were confirmed using qRT-PCR. We found that plant miRNAs targeted fungal virulence genes, while fungal milRNAs targeted plant resistance genes; corroborating miRNA-mediated trans-kingdom gene regulation and the roles of miRNAs in plantpathogen interactions. Transgenic plants with miRNAs targeting fungal virulence genes, or anti-sense of fungal milRNAs, would be expected to be highly resistant to the fungal pathogens.
Keywords: Disease resistance; Fungal miRNAs; qRT-PCR; Resistance genes; Target prediction; Virulence genes

Role of jasmonate in modulation of mycorrhizae-induced resistance against fungal pathogens - Nair, Aswathy; Thulasiram, H. V.; Bhargava, Sujata (Methods in Molecular Biology, 2020)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Symbiotic association of plants with arbuscular mycorrhizal (AM) fungi brings about changes in levels of the phytohormone jasmonate (JA) in root and shoot tissues of a plant. The enhanced JA levels not only play a role in controlling the extent of AM colonization but are also involved in the expression of mycorrhizal-induced resistance (MIR) against pathogens. We describe a method used to study the levels of a volatile jasmonate derivative, methyl jasmonate (MeJA), in tomato plants colonized by AM fungi and in response to subsequent attack by the foliar pathogen Alternaria alternata.